Personal health records : a guide for clinicians - Al-Ubaydli, Mohammad (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell, 2011)
'Patient-controlled personal health records are the key to successful interaction between physician and patient. They form the core for joined-up communication throughout health organizations. Still, the very name is capable of alarming both patient and doctor. Are they reliable? Are they complete? Are they confidential? Where do you access them? For the doctor, additional concerns surround the implementation: how do you include these online tools in your busy schedule? How much will they add to your existing spend on information technology? Can you get paid for doing all this extra work? Now you can find dependable answers to all of these questions. Written by a physician who has developed his own personal health records software for patients and doctors to interact, Personal Health Records: A Guide for Clinicians explains how to get the best from your patient's records and how to put the information to good use, helping both your patient and yourself to a more effective and efficient outcome in any clinical situation'--Provided by publisher.
Front Matter -- Your Patients. Part Introduction -- Sharing Data with your Patient -- Protecting your Patient's Privacy -- Patient Communities -- Your Work. PHRs and Clinical Teams -- Educating Patients -- Saving Time in your Clinic -- Your Practice. Technology -- Law -- Finance -- The Future -- Appendices. Appendix A: Google Health -- Appendix B: Microsoft HealthVault -- Index.
Includes bibliographical references and index.
Keywords: Medical records -- Management; Personal information management; Forms and Records Control -- methods; Medical Records Systems, Computerized -- organization & administration; Communication; Patient Access to Records; Physician-Patient Relations; MEDICAL -- Medical History & Records; Medical records -- Management; Personal information management; Electronic books